Egg transport and larval behavior of curimba, Prochilodus lineatus (Valenciennes, 1836; Characiformes, Prochilodontidae) in a drift simulator channel - Thays Cristine Bellenzier de Queiroz; Dirceu Baumgartner; Pitágoras Augusto Piana; Paulo Vanderlei Sanches (Acta Scientiarum. Biological Sciences, 2022)
Landscape changes and hydrologic alterations associated with dam construction have greatly hindered reproductive success and the recruitment of migratory species. However, little is known about the flow conditions that are necessary for the reproductive success of migrators. We aimed to analyze one of the important migrants of the Paraná River, the curimba, Prochilodus lineatus (Valenciennes, 1836), to determine the minimum velocities necessary for egg drift and analyze the behavior of larvae at different flow velocities. Thus, we experimentally evaluated the behavior of eggs and larvae released in a drift simulator channel (DSC) under four flow velocities. Additionally, we investigate the swimming ability of larvae in relation to certaintheirarvaeng ability in relation to asures of larval body to their ability ased in a Drift Simulator Channel certaincerrain morphometric measures of their bodies. We also performed morphometry and calculations of larval body and fin proportions to determine which structures influence swimming ability. The results indicated that environments with flow velocities greater than 0.081 m s-1 were favorable for egg drift and increased the chances of successful transport of eggs to downstream areas. We also observed that soon after hatching, the larvae positioned themselves against the flow, indicating that they had a perception of position and orientation. The larvae were able to maintain and disperse against the flow within the channel 32h after hatching at all velocities, which was mainly due to the development of pectoral and caudal fins that were actively involved in the swimming process, as well as the reduction in the dimensions of the yolk sac, which reduced drag.